Social media enhanced boundary crossing: exploring distance students' ecosystems of learning support - Mwanda, Ziyanda (School of Education, 2021)
As the demand for distance learning increases, traditional campus-based universities continue to struggle in supporting working distance students. This has resulted in the increased phenomena of students using social media within their ecosystems of learning support. The use of formal and informal tools such as social media gives rise to boundaries which students need to cross for effective support. How social media facilitates the crossing of boundaries within ecosystems of learning support remains an unfamiliar area of research. This study employed a predominately qualitative research methods, with a small element being a quantitative method to view and investigate postgraduate distance students' ecosystem of learning support holistically. The findings of this study revealed that participants used a combination of formal and informal tools to support their learning, including social media. In particular WhatsApp, which enables the crossing of transitional, formal and informal learning contexts, hierarchical and, time and space boundaries. Recognizing social media as an important part of students' learning support ecosystem, allowed an expanded view on learning support. As such, the study highlighted a range of different learning mechanisms which occur when students cross these boundaries, with coordination being the dominant learning mechanism. In conclusion, social media (such as WhatsApp) does indeed enhance the crossing of various boundaries to support learning. However, some students do not necessarily perceive their interaction on social media as learning, which speaks to the need of legitimising social media as learning tools by institutions. This study then recommends the need for institutions to recognize and nurture the use of social media as one element of a distance learning support ecosystem for cost-effective student support strategies guided by institutional guidelines and policies.